2014
DOI: 10.1158/1055-9965.epi-13-1064
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Completion Rates among African Americans in a Randomized Effectiveness Trial for Diet and Physical Activity Changes

Abstract: Background The intervention completion rate is an important metric in behavioral and intervention research; trials with limited intervention completion rates may have reduced internal validity. We examined intervention completion rates among 530 African Americans who had been randomized to an integrated (INT) or disease-specific (DSE) risk education protocol as part of a comparative effectiveness trial from September 2009 to August 2012. Methods The interventions were developed by an academic-community partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Additional research is needed to evaluate the impact of FHH education programs on the collection of this information and to identify the most effective setting for delivering these types of programs to men. Recently, we found that African American men were as likely as women to complete a community-based risk education program about cancer and cardiovascular disease (Halbert et al 2014;Wu et al 2013). Community-based programs may be an effective setting for delivering education about the importance of FHH collection and strategies for obtaining this information to men.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to evaluate the impact of FHH education programs on the collection of this information and to identify the most effective setting for delivering these types of programs to men. Recently, we found that African American men were as likely as women to complete a community-based risk education program about cancer and cardiovascular disease (Halbert et al 2014;Wu et al 2013). Community-based programs may be an effective setting for delivering education about the importance of FHH collection and strategies for obtaining this information to men.…”
Section: Discussionmentioning
confidence: 99%
“…African American men may be under-represented in clinical research [ 21 ], but there are some examples of successful recruitment of African American men in both genetic and non-genetic studies. Relative to women, African American men had similar rates of participating in a lifestyle intervention that was designed to increase motivation to change diet and physical activity [ 22 ]. Similarly, the African American Hereditary Prostate Cancer (AAHPC) [ 23 ] study enrolled 92 African American high risk families and complete clinical data were available on 154 African American men who had a personal history of prostate cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…38 Most cancer-based CBPR interventions focus on screening for cancer to combat health disparities, 39,40 promotion of general overall health, 41 or participation rates among AAs. 42 The SISTAS trial is unique for several reasons. Most importantly, it is one of the only RCTs of dietary and physical activity among African American women that measured biological biomarkers of disease (inflammatory markers).…”
Section: Interventions That Are Personalizedmentioning
confidence: 99%